Physiological and performance effects of live high train low altitude training for elite endurance athletes: A narrative review - Bonato, G.; Goodman, S. P. J.; Lathlean, T. (Current Research in Physiology, 2023)
Altitude training has become an important training application for athletes due its potential for altering physiology and enhancing performance. This practice is commonly used by athletes, with a popular choice being the live high - train low approach. This model recommends that athletes live at high altitude (1250-3000 m), but train at low altitude or sea-level (0-1200 m). Exposure to altitude often leads to hypoxic stress and in turn stimulates changes in total haemoglobin mass, erythropoietin, and soluble transferrin receptors, which alter further underlying physiology. Through enhanced physiology, improved exercise performance may arise through enhancement of the oxygen transport system which is important for endurance events. Previous investigations into the effects of altitude training on exercise performance have been completed in a range of contexts, including running, cycling, swimming, and triathlon. Often following a LHTL altitude intervention, athletes realise improvements in maximal oxygen consumption capacity, time trial performance and peak power outputs. Although heterogeneity exists among LHTL methodologies, i.e., exposure durations and altitude ranges, we synthesised this data into kilometre hours, and found that the most common hypoxic doses used in LHTL interventions ranged from ~578-687 km h. As this narrative review demonstrates, there are potential advantages to using altitude training to enhance physiology and improve performance for endurance athletes.